Algerian criminal policy between the positive movement and legal stability and its impact on the moral base. - Litouche, Dalila (Journal of Human Sciences, 2021)
The criminal policy varies between a Western and a legitimate situation. Although both are trying to tackle the crime of all kinds, there are fundamental differences between them in terms of principles and constants that have affected the reality of punitive application. The legislator tried to fight crime according to the French legal inheritance that proved its failure in reality. Evidence of the continued growth of crime, and a legitimate inheritance derived from the Koran and Sunnah, and if he found that the latter tended to think positive Western positive when the majority of acts, and it would be better to pursue a legitimate criminal policy with established principles to eliminate crime and preserve values.